NEGOTIATING THE RULE OF LAW AND HUMAN RIGHTS IN INTERFAITH MARRIAGE REGISTRATION IN CONTEMPORARY INDONESIA - Salam, Nor; Zaman, Jamrud Qomaruz (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2024)
The Supreme Court Circular Letter Number 2 of 2023, which prohibits the registration of interfaith marriages in Indonesia, aims to provide legal clarity following longstanding debates fueled by the abstract nature of existing norms. While the circular seeks to enforce uniformity in marriage regulations, it raises concerns regarding human rights, especially the rights to freedom, equality, and the pursuit of happiness, which are central to democratic governance. This article seeks to examine interfaith marriage registration by utilizing normative and human rights perspectives to explore its legal foundations and implications within Indonesia’s modern context. The analysis highlights tensions between national law and international human rights conventions, suggesting that interfaith marriage registration should be recognized as a legal right that upholds citizens’ freedoms, religious autonomy, and equality before the law. By situating interfaith marriage within Indonesia’s framework of Islamic jurisprudence (fiqh), legal statutes, and human rights conventions, this article highlights the importance of balancing legal uniformity with the protection of individual rights in a democratic, constitutional state.